Stress in utero: prenatal dexamethasone exposure causes greater structural gliovascular alterations in female offspring than in males - Ferreira-Rodrigues, Magda; Sousa, Inês Santos; Baptista, Filipa I.; Coelho-Santos, Vanessa (Frontiers in Neuroscience, 2025)
From early in life, experiences like prenatal stress profoundly affect long-term health and behavior. Fetal exposure to increased levels of glucocorticoids (GC), via maternal stress or through antenatal corticosteroid therapy (commonly used in women at risk of preterm birth), can disrupt brain development and raise the susceptibility to psychiatric disorders. Previous studies on prenatal exposure to synthetic GCs, such as dexamethasone (DEX), revealed impairments in neurogenesis and dendritic spine development. However, the impact of prenatal stress, specifically antenatal DEX exposure, on the gliovascular interface remains unclear. This interface, involving the relationship between astrocytes and blood vessels, is essential for healthy brain development. Astrocytic endfeet coverage and organization are crucial features of the gliovascular interface, and in this study, we evaluated these aspects through aquaporin-4 (AQ4) expression and organization along the lectin labelled-vasculature. At Postnatal Day 14, no differences in AQ4 expression were observed between males and females. However, prenatal stress induced by DEX exposure (50 μg/kg was administered subcutaneously to pregnant mice through gestational days 16, 17 and 18) significantly impacted this structure in females but not in males. Specifically, in female offspring prenatally exposed to DEX, AQ4 expression was significantly upregulated in the hippocampus, and its rearrangement was observed in the prefrontal cortex. A comparison of vascular density between male and female brains showed no significant sex differences in any analyzed regions, though male cerebellar vessel segments were shorter. Interestingly, prenatal stress caused morphological alterations in female brains, including increased vessel tortuosity, while no such changes were seen in males. In the hippocampus, prenatal DEX exposure reduced vessel segment length in males but did not affect females. In the cerebellum, DEX exposure increased vessel segment length in females. This study highlights sex-specific differences in the impact of prenatal stress on the gliovascular structure across various brain regions, suggesting AQ4 as a potential molecular target relevant to depressive-like behaviors in female offspring. Future studies are needed to correlate the gliovascular structural alterations found with functional disturbances and sex-specific mental health issues.